The interaction between standards development and economic growth of China - Hao Zhang; Jiadong Jiang; Liwei Zheng; Xiangzhen Li (International Journal of Quality Innovation, 2019)
China has been participating in the international standards activities since the reform and opening up period. China's standards action has not only brought about significant changes in the way of international trade, but also changed the connotation and manifestation of economic growth, which has further affected China's position in the world standards development. On the basis of qualitative analysis of the interaction between standards development and economic growth, this paper quantitatively analyzes the degree of interaction between them. The results indicate that the higher standards in a country, the stronger its economic strength and the higher its position in world standards development. This conclusion is helpful for the government, industry authorities, and enterprises to pay more attention to standards in quality management and improve the standards level.
Keywords: 650; Standards; Economic growth; Technological innovation; China; Quality assurance